Taxa of Families Asclepiadaceae and Periplocaceae not Represented in Indian Herbaria - Jagtap, A. P.; Singh, N. P. (Indian Forester, 1997)
24 taxa of family Asclepiadaceae and a solitary one of Periplocaceae not represented in Indian herbaria are enumerated in the present paper.